2018
DOI: 10.1177/1042258718812185
|View full text |Cite
|
Sign up to set email alerts
|

What’s Love Got to Do With It? Team Entrepreneurial Passion and Performance in New Venture Teams

Abstract: We integrate literatures on entrepreneurial passion, shared emotions, and group identities to extend a conceptual model of team entrepreneurial passion (TEP). We delineate mono-focal, complete, and incomplete poly-focal TEP, and examine how each type and focus of TEP is related to team performance. We test our hypotheses with 73 new venture teams. Results reveal that TEP occurs in 61 teams in our sample (23 mono-focal, 26 complete poly-focal, 12 incomplete poly-focal). In terms of focus, TEP for inventing and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
72
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(80 citation statements)
references
References 75 publications
2
72
0
Order By: Relevance
“…A general affective state of entrepreneurial passion implanted within a particular context is likely to result in an operation situated in an entrepreneurial spirit that strengthens any marketing decisions taken during COVID-19. It thus appears to be consistent to predict that entrepreneurial passion can lead people towards decisions (Treffers et al 2017 ; Santos and Cardon 2019 ; Murnieks et al 2020 ). In this case, it is now easy to understand that technology also increases entrepreneurial passion which later contributes to marketing decisions.…”
Section: Literature Review and Hypothesis Developmentsupporting
confidence: 74%
See 1 more Smart Citation
“…A general affective state of entrepreneurial passion implanted within a particular context is likely to result in an operation situated in an entrepreneurial spirit that strengthens any marketing decisions taken during COVID-19. It thus appears to be consistent to predict that entrepreneurial passion can lead people towards decisions (Treffers et al 2017 ; Santos and Cardon 2019 ; Murnieks et al 2020 ). In this case, it is now easy to understand that technology also increases entrepreneurial passion which later contributes to marketing decisions.…”
Section: Literature Review and Hypothesis Developmentsupporting
confidence: 74%
“…Being passionate about entrepreneurship in general may be a catalyst in starting a company. As a result, individuals who are passionate about an entrepreneurial career are likely to build up an intention to start a company (Chen et al 2009 ; Miller et al 2012 ; Santos and Cardon 2019 ; Hubner et al 2019 ).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Entrepreneurial passion is associated with positive feelings and attitudes for activities that are crucial to the self-identity of the individual ( Huyghe et al, 2016 ). Passion is considered as the heart of entrepreneurship and it can become a vital component of entrepreneurial behavior action as well as the business creation process and its outcomes ( Cardon et al, 2013 ; Santos and Cardon, 2019 ). According to Vallerand et al (2003) , passion is associated with the strong feeling to perform any task that individuals like to achieve with full energy.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Control variables that may confound the hypothesized relationships were chosen in this study. Team size and team tenure were controlled because they may exert influences on entrepreneurial team heterogeneity and functioning (Gonzalez-Cruz et al, 2020; Santos & Cardon, 2019). Also, industrial type was controlled because it is suggested to affect the resource requirement or strategy implementation of entrepreneurial teams (Zhou et al, 2015).…”
Section: Methodsmentioning
confidence: 99%